b x 6 +18 =24
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 24 : 6 : 2 = 4 : 2 = 2 => Đ
b) 24 : 6 : 2 = 24 : 3 = 8 => S
c) 18 : 3 x 2 = 18 : 6 = 3 => S
d) 18 : 3 x 2 = 6 x 2 = 12 => Đ
a) 6 x 5 = 30 30 : 6 = 5 30 : 5 = 6
b) 6 x 3 = 18 18 : 6 = 3 18 : 3 = 6
c) 6 x 4 = 24 24 : 6 = 4 24 : 4 = 6
5 x 6 = 30 2 x 6 = 12 3 x 6 = 18 4 x 6 = 24
6 x 5 = 30 6 x 2 = 12 6 x 3 = 18 6 x 4 = 24
a: \(\dfrac{-4}{8}=\dfrac{x}{-10}=\dfrac{-7}{y}=\dfrac{z}{-24}\)
=>\(\dfrac{x}{-10}=\dfrac{-7}{y}=\dfrac{z}{-24}=\dfrac{-1}{2}\)
=>\(\left\{{}\begin{matrix}x=\left(-10\right)\cdot\dfrac{\left(-1\right)}{2}=5\\y=\dfrac{-7\cdot2}{-1}=14\\z=\dfrac{-24\cdot\left(-1\right)}{2}=\dfrac{24}{2}=12\end{matrix}\right.\)
b: \(\dfrac{-3}{6}=\dfrac{x}{-2}=\dfrac{-18}{y}=\dfrac{-z}{24}\)
=>\(\dfrac{x}{-2}=\dfrac{-18}{y}=\dfrac{z}{-24}=\dfrac{-1}{2}\)
=>\(\dfrac{x}{2}=\dfrac{18}{y}=\dfrac{z}{24}=\dfrac{1}{2}\)
=>\(x=2\cdot\dfrac{1}{2}=1;y=18\cdot\dfrac{2}{1}=36;z=\dfrac{24}{2}=12\)
a)
x . 6 + 18 = 24
x . 6 = 24 - 18
x . 6 = 6
x = 6 : 6
x = 1
Vậy x = 1
b)
6 . x - 12 = 36
6 . x = 36 + 12
6 . x = 48
x = 48 : 6
x = 8
Vậy x = 8
c)
x : 6 + 15 = 20
x : 6 = 20 - 15
x : 6 = 5
x = 5 .6
x = 30
Vậy x = 30
d)
54 : x + 20 = 29
54 : x = 29 -20
54 : x = 9
x = 54 : 9
x = 6
Vậy x = 6
Học tốt!!!
a)X * 6 +18=24
X*6 = 24-18
X*6 = 6
X= 6:6
X=1
b)6 * x -12=36
6*X= 12 +36
6*X = 48
X= 48 :6
X= 8
c)x : 6 +15=20
X:6 = 20-15
X:6 = 5
X= 5*6
X=30
d)54 : x +20=29
54 :X = 29-20
54 : X = 9
X= 54 :9
X= 6
\(\frac{x^{24}+x^{18}+x^{12}+x^6+1}{x^{27}+x^{24}+x^{21}+x^{18}+x^{15}+x^{12}+x^9+x^6+x^3+1}=\frac{x^{24}+x^{18}+x^{12}+x^6+1}{x^{24}\left(x^3+1\right)+x^{18}\left(x^3+1\right)+x^{12}\left(x^3+1\right)+x^6\left(x^3+1\right)+\left(x^3+1\right)}\)
=\(\frac{x^{24}+x^{18}+x^{12}+x^6+1}{\left(x^3+1\right)\left(x^{24}+x^{18}+x^{12}+x^6+1\right)}=\frac{1}{x^3+1}\)
bx6+18=24
bx6=24-18
bx6=6
b=6:6
b=1